Striatal FoxP2 is actively regulated during songbird sensorimotor learning. - Ikuko Teramitsu; Amy Poopatanapong; Salvatore Torrisi; Stephanie A White (PLoS ONE)
Background Mutations in the FOXP2 transcription factor lead to language disorders with developmental onset. Accompanying structural abnormalities in cortico-striatal circuitry indicate that at least a portion of the behavioral phenotype is due to organizational deficits. We previously found parallel FoxP2 expression patterns in human and songbird cortico/pallio-striatal circuits important for learned vocalizations, suggesting that FoxP2's function in birdsong may generalize to speech. Methodology/principal findings We used zebra finches to address the question of whether FoxP2 is additionally important in the post-organizational function of these circuits. In both humans and songbirds, vocal learning depends on auditory guidance to achieve and maintain optimal vocal output. We tested whether deafening prior to or during the sensorimotor phase of song learning disrupted FoxP2 expression in song circuitry. As expected, the songs of deafened juveniles were abnormal, however basal FoxP2 levels were unaffected. In contrast, when hearing or deaf juveniles sang for two hours in the morning, FoxP2 was acutely down-regulated in the striatal song nucleus, area X. The extent of down-regulation was similar between hearing and deaf birds. Interestingly, levels of FoxP2 and singing were correlated only in hearing birds. Conclusions/significance Hearing appears to link FoxP2 levels to the amount of vocal practice. As juvenile birds spent more time practicing than did adults, their FoxP2 levels are likely to be low more often. Behaviorally-driven reductions in the mRNA encoding this transcription factor could ultimately affect downstream molecules that function in vocal exploration, especially during sensorimotor learning.